ANISOTROPY OF ELECTRICAL-PROPERTIES IN ALPHA-FE2O3 CERAMICS - Santilli, Celso Valentim [UNESP]; Bonnet, J. P.; Dordor, P.; Onillon, M. (Chapman Hall Ltd, 1993)
Electrical conductivity and thermoelectric power measurements carried out in a heamatite ceramic showed a strong anisotropy in directions normal and parallel to the uniaxial pressing direction. This behaviour is similar to that verified in alpha-Fe2O3 single crystal. The results suggest that the extended structural defects, generated during sintering, disturb the magnetic order on the (001) planes of alpha-Fe2O3 and limit the mobility of n type carriers.